(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
This article analyzes the symbols and images related to natural phenomena in Uzbek folk proverbs from a linguocultural perspective. The spiritual content expressed in folk thinking through images of natural phenomena - hail, rain, winter, summer, cold, as well as animal names (arkar, cow, sheep, rabbit) is revealed. The denotative and connotative meanings of proverbs are analyzed, and it is shown that they were formed as symbols reflecting the attitude of the people to life, labor, patience, prosperity and trials.